Business Plan (2017 - 2022) Drivers Co. Ltd. - Phan, Bao (2016)
“Drivers” is offering 25% of the shares in exchange for 100,000 USD from year 1. This is the amount of additional funding that we need for our daily operation activities of the company in the first year and the second year to generate the net profits of 28,622 USD in year 2 (0.98% net profit margin), 222,608 USD in year 3 (3.89% net profit margin) and 461,787 USD in year 4 (5.38% net profit margin) and 734,958 USD in year 5 (6.41% net profit margin). At the end of year 5, our management team will return the total of 486,993 USD to investors, including 25% of profits per year plus 25% R.O.E.